2007
DOI: 10.1021/bi701460x
|View full text |Cite
|
Sign up to set email alerts
|

Heme Synthase (Ferrochelatase) Catalyzes the Removal of Iron from Heme and Demetalation of Metalloporphyrins

Abstract: The red pigments in meat products, including cooked cured ham, arise from the reaction of myoglobin with nitric oxide generated from exogenous nitrite. Since carcinogenic nitrosoamines may be generated by the treatment of meats with nitrite, the production of nitrite-free meat products is an attractive alternative. Raw dry-cured (Parma) hams are produced by the treatment of meats with salts other than nitrite. Analysis of pigments in raw dry-cured hams reveals that the main pigment is zinc protoporphyrin, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 27 publications
0
57
0
2
Order By: Relevance
“…In 2 cases, ferrochelatases from meat (21) and from Haemophilus influenzae (22) have been shown to catalyze the reverse reaction in vitro in the presence of reductants. However, YfeX and EfeB do not have significant sequence similarities to any known ferrochelatase and thus most likely have evolved separately to achieve the reaction by a mechanism distinct from ferrochelatases.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 cases, ferrochelatases from meat (21) and from Haemophilus influenzae (22) have been shown to catalyze the reverse reaction in vitro in the presence of reductants. However, YfeX and EfeB do not have significant sequence similarities to any known ferrochelatase and thus most likely have evolved separately to achieve the reaction by a mechanism distinct from ferrochelatases.…”
Section: Discussionmentioning
confidence: 99%
“…Hemin-imidazole was prepared as previously described. 10) Pig kidney LLC-PK1 cells were obtained from the Japan Cell Bank (Saitama, Japan). Porcine livers and muscles were generously donated by Itoh Ham Inc. (Moriya, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…8,9) Therefore, reutilization of iron, including degradation of the heme, catalyzed by heme oxygenase, is essential for the homeostasis of iron in cells. Recently, we reported that the removal of ferrous ions from heme occurred in vivo, and that FECH removed iron from heme in vitro, 10) but the role of the reaction in removing iron in vivo is not clear.…”
mentioning
confidence: 99%
See 2 more Smart Citations